2021
DOI: 10.32672/jse.v6i3.3120
|View full text |Cite
|
Sign up to set email alerts
|

Pengolahan Sampah Organik dan Limbah Biomassa dengan Teknologi Olah Sampah di Sumbernya

Abstract: Solid Waste Processing Technology at the Source (TOSS) is an alternative method in processing organic and biomass waste on a communal scale. The processing of organic and biomass waste material is carried out in three stages of the process: biodrying which utilizes the aerobic activity of microorganisms; chopping which is intended to refine the material, and pelletization to compact the material into biomass pellets. The biodrying process in bamboo boxes is able to reduce the water content in organic and bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Based on field studies during the biodrying process using the AR124, the moisture level of domestic organic waste decreased from 43.50% to 39.40% on the fourth day. The moisture level further decreased to 32.23% after the fifth day [3].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Based on field studies during the biodrying process using the AR124, the moisture level of domestic organic waste decreased from 43.50% to 39.40% on the fourth day. The moisture level further decreased to 32.23% after the fifth day [3].…”
Section: Introductionmentioning
confidence: 93%
“…The process of processing leaf and twig waste using the TOSS method was carried out in triplicate with three variations of biodrying without addition of bioactivators (control, with AR124 addition, and with MOL addition). The process mechanism was based on the research by Brunner et al [3] and follows the following stages: shredding, biodrying, pelletization, product finalisation (sun-dried).…”
Section: Waste Processing With On-site Solid Waste Processing Technol...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ecobrick menjadi efektif dalam mengurangi sampah plastik (Sunandar et al, 2020). mikroorganisme, proses pencacahan (pemilihan kembali hasil biodrying sebelum masuk ke dalam mesin cacah), proses peletisasi (pemadatan hasil pencacahan) (M. Brunner et al, 2021).…”
Section: Ranksunclassified
“…TOSS technology has garnered attention for its potential to mitigate waste accumulation at its origin while simultaneously generating a reusable resource. Brunner et al, [3] in their research reported that the biomass produced by TOSS technology with the diameter of 10 mm and the length of 10 -40 mm has a colorific value between 3000 -4000 kcal/kg.…”
Section: Introductionmentioning
confidence: 99%